Leven als zoekpartij Intergenerationele zingeving en spiritualiteit - Smeets, Wim (Radboud University Press, 2023)
People are now more liberated to give meaning to their life and to select values they deem important. What effect does this have on conversations about meaning and spirituality with the upcoming generation? Nowadays, shared religious and church practices are not as prevalent as they once were. Is a personal testimony of how meaning and spirituality have developed in one's own life the or a way of communicating something to children, pupils, and students? One way of sharing a testimony is the 'spiritual autobiography', a practice that was developed in the US and later brought to the Netherlands by Jannet Delver. It is now used in universities and higher vocational schools. Also for group discussions with clients, writing and sharing one's spiritual biography has been found to contribute to (re)finding sources of strength in difficult times. In this book, the method is applied in an intergenerational context through a series of letters between the editor and his daughters Elsemarijn and Janneleen, along with an accompanying discussion. Additionally, many professionals and scientists provide their - personal - perspectives. Living as a search for the meaning of life need not be laborious, but rather engaging and contagious.